1932 : FDR, Hoover and the dawn of a New America - Martelle, Scott, 1958- (Citadel Press, Kensington Publishing Corp., 2023)
"In one vitally significant year in American history, the country would experience turmoil, instability, natural disaster, bubbling political radicalism, and a rise of dangerous forces ushering in a new era of global conflict--and emerge both afresh and revitalized. At the start of 1932, the nation's worst economic crisis has left one-in-four workers without a job, countless families facing eviction, banks shutting down as desperate depositors withdraw their savings, and growing social and political unrest from urban centers to the traditionally conservative rural heart of the country. Amid this turmoil, a political decision looms that will determine the course of the nation. It is a choice between two men with very diferent visions of America: Incumbent Republican Herbert Hoover with his dogmatic embrace of small government and a largely unfettered free market, and New York's Democratic Governor Franklin Delano Roosevelt and his belief that the path out of the economic crisis requires government intervention in the economy and a national sense of shared purpose. Now veteran journalist Scott Martelle provides a gripping narrative retelling of that vitally significant year as social and political systems struggled under the weight of the devastating Dust Bowl, economic woes, rising political protests, and growing demand for the repeal of Prohibition. That November, voters overwhelmingly rejected decades of Republican rule and backed Roosevelt and his promise to redefine the role of the federal government while putting the needs of the people ahead of the wishes of the wealthy. Deftly told, this illuminating work spotlights parallel events from that pivotal year and brings to life figures who made headlines in their time but have been largely forgotten today. Ultimately, it is the story of a nation that, with the help of a leader determined to unite and inspire, took giant steps toward a new America"--